Application of PSIM Software-Assisted Demonstration Method in Basic Subjects and Electricity Measurement Class X Titl at SMK Negeri 2 Banda Aceh - Sri Safiatuddin; Rizki Julia Utama; Fira Julianda; Rahmat Fajri; Rahmat Alimin; Muhammad Rizki; Rizki Makhrifandi (CV. Edujavare Publishing, 2026)
This study examines the application of the demonstration method assisted by Psim Software to improve the learning outcomes of class X TITL students at SMK Negeri 2 Banda Aceh. The study was motivated by the ineffectiveness of the teaching and learning process and the low learning outcomes of many students. This quantitative research employed a pre-experimental control-group pretest-posttest design. Data were collected through pretests, posttests, and questionnaires, and analyzed using an independent-samples t-test with SPSS. The results indicate a significant difference in student learning outcomes before and after the implementation of the demonstration method. The average posttest score of the experimental group was higher than that of the control group (74.66 compared with 59.33). The equality of variance test showed that the two groups had homogeneous variances. Furthermore, the significance value of the two-tailed t-test was 0.03, which was lower than the significance level of 0.05. Therefore, the null hypothesis was rejected. These findings demonstrate that the demonstration method assisted by Psim Software can effectively improve the learning outcomes of class X TITL students at SMK Negeri 2 Banda Aceh.